Decline and Bidecadal Oscillations of Dissolved Oxygen in the Oyashio Region and Their Propagation to the Western North Pacific. Issue 6 (6th June 2018) - Sasano, Daisuke; Takatani, Yusuke; Kosugi, Naohiro; Nakano, Toshiya; Midorikawa, Takashi; Ishii, Masao
Abstract: During the period 1954–2014, concentrations of dissolved oxygen (O2 ) in the Oyashio region of the western subarctic North Pacific has been oscillating over bidecadal timescales and significantly decreasing over the isopycnal layer spanning σθ = 26.6–27.5 kg/m 3 . The cycles of oscillation (16.4–19.6 years) are almost consistent and synchronized within 1 year over this density layer and are probably controlled by the nodal tidal cycle of 18.6 years and/or atmospheric forcing. The mean rate of the long‐term decrease is the highest (−0.70 ± 0.06 μmol · kg −1 · year −1 ) in the temperature minimum layer. The O2 decline there is predominantly attributed to a reduction of ventilation in winter due to warming and freshening. On the other hand, the O2 decline in deeper layers down to the oxygen minimum layer is attributable to a reduction in ventilation in the Sea of Okhotsk associated with a reduction in sea ice formation and propagation of its impact through diapycnal mixing adjacent to the Bussol' Strait. These trends of bidecadal oscillations and decline of O2 were also found in the downstream to the east in the 165°E section at latitudes 30°N–42.5°N on σθ = 26.8 kg/m 3 and with attenuated amplitudes at latitudes of 40°N–45°N in the oxygen minimum layer on σθ = 27.4 kg/m 3 . These results indicate that the signal of secular declines of O2, together with bidecadal oscillations, is being propagated broadly from the Oyashio source region into the interior of the Pacific Ocean. Key Points: Decline of dissolved O2 has been observed in the Oyashio region for the past 61 years on isopycnal surfaces of σθ = 26.6–27.5 kg/m 3 Bidecadal oscillations of O2 were found on these isopycnals and could be explained by the nodal tidal cycle and/or atmospheric forcing Bidecadal oscillations propagating from the Oyashio region were also found along 165 degrees E with smaller amplitude together with an O2 decline